Community attachment, tourism impacts, quality of life and residents’ support for sustainable tourism development - Eslami, Sadraddin (Routledge, 2019)
This study examined the formation of residents’ support for sustainable tourism development based on the social exchange theory and bottom-up spillover theory. A self-administered survey along with a structural analysis was used. Our result revealed that overall quality of life satisfaction influenced support for sustainable tourism development, and that material life domains and non-material life domains were two important determinants of overall QoL. Perceived sociocultural impacts of tourism had a significant relationship with non-material life domains. Perceived economic impacts of tourism influenced both material and non-material life domains. Community attachment and residents’ perceived impacts of tourism were significantly associated.